Spatiotemporal dynamics and driving mechanisms of total factor carbon productivity in China's provincial transportation sector - Sun, Yanming; Liu, Jiale; Li, Qingli (Frontiers in Climate, 2025)
Enhancing transportation total-factor carbon productivity constitutes a critical initiative for high-quality economic development across Chinese provinces. Based on panel data from 30 Chinese provinces spanning 2007–2022, this study comprehensively employs the Super-Efficiency Slack-Based Measure (SBM) model, non-parametric kernel density estimation, standard deviational ellipse, and global Moran's I index to analyze the spatiotemporal evolution characteristics of Total Factor Carbon Productivity in Transportation (TFCP-T) across provinces. Finally, a spatial Durbin model is utilized to empirically investigate influencing factors. Key findings include: (1) China's provincial TFCP-T exhibits an overall fluctuating upward trend, yet reveals a distinct spatiotemporal differentiation pattern characterized by “high efficiency and intensification in the eastern region versus gradient lag in the central and western regions.” (2) Significant spatial positive correlation and club convergence effects exist in China's transportation green total factor productivity, with western provinces facing risks of low-level lock-in. (3) Economic development level, openness to foreign trade, environmental protection intensity, and industrial structure upgrading positively promote TFCP-T, while consumption level and informatization level exert significant inhibitory effects. These results provide critical policy insights for enhancing transportation carbon productivity and fostering regional coordinated development in China.